EVALUATE THE PRESENCE OF BUTTERFLY EFFECT IN THE TRANSVERSE SECTIONS OF THE ROOTS OF INCISORS, CANINES AND PREMOLARES - Santhanam, Archana; N, Shivani (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
Aim: To evaluate the presence of butterfly effect in the transverse sections of the roots of incisors, canines and premolars. Background: The butterfly effect is an optical phenomenon seen generally in the cross sections of root under light microscope. It occurs due to the change in the dentinal tubule density which causes light to refract and scatter when passed through it. Materials and Methods: A total of 30 single rooted freshly extracted teeth without any caries and fractures were selected and were grouped in three groups (Group I =10 incisors, Group II =10 canines, Group III premolars respectively). Using a Micro motor and a diamond abrasive bur, the crowns were decoronated and the root were sectioned into 3 transverse sections.  Each section is made into 1mm uniform thickness and were observed under light microscopy to detect the presence or absence of butterfly effect and the scoring was given accordingly. Results: 90% of incisors and canines showed butterfly effect, whereas only 20% of the premolars showed the effect. The butterfly effect was found to be more in the buccolingual direction than in the mesiodistal direction. Conclusion: The presence of butterfly effect in transverse sections of root helps in understanding the root fractures which has its significance in endodontics during instrumentation.